Metaverse Workspaces for Active Learning - Brazilian Oil & Gas Company case - Azevedo, Delmir P.; Muniz, Jorge [UNESP]; Campos, Renato [UNESP] (My University, 2023)
The digitization of the economy, already quite advanced before 2020, accelerated significantly during the pandemic. Restrictions on holding face-to-face educational events during this period stimulated the development of its virtual and hybrid versions, bringing new challenges to workforce skills development. This paper discusses the use of 3D virtual environments and Metaverse in carrying out workforce training events, including considerations about pre, during or postevent, from the knowledge management perspective and a SWOT based on a multidisciplinary approach. A Brazilian Oil & Gas Company case supports the discussion with lessons learned from three events involving 8,000 people and more than 104,000 man-hours of participation. The findings highlight the democratization of access to knowledge, the innovatiońs effectiveness in knowledge management with 90% satisfaction among the participants and favourability of 74% regarding the capacity for interaction between the participants in active learning activities.
Keywords: Active Learning; Conferences; Immersive learning; Knowledge Management; Metaverse